From Deformation to Hydrology A Comparative Evaluation of InSAR and Modelling Techniques for Assessing Water Availability in Varied Hydrological Systems - Khodaei, Behshid ; 0000-0001-7093-7614 (Department of Building and Environmental Technology, Lund University, 2025)
Water resources are under increasing pressure from population growth, climate change, and intensified human activity. Effective water management requires a clear understanding of both surface and subsurface hydrological systems, yet traditional monitoring methods often fall short in spatial and temporal coverage. Interferometric Synthetic Aperture Radar (InSAR), a satellite-based remote sensing technology, offers a powerful means to detect surface deformations linked to changes in groundwater storage. This dissertation explores the use of InSAR to monitor land subsidence, infer aquifer properties such as storativity, and enhance groundwater modelling in data-scarce, agriculturally intensive regions. By integrating InSAR with machine learning and physically-based models, the research enables improved estimation of groundwater levels and aquifer behaviour. It also examines the interactions between surface water and groundwater, emphasizing the importance of integrated management strategies. Overall, this work highlights InSAR's value in advancing scalable, data-driven approaches to sustainable water resource monitoring and decision-making.